The valid nomen for the tree frog (genus Hyla) of Tunisia and Eastern Algeria - Dufresnes, Christophe; Crochet, Pierre-André (Zootaxa, 2020)
Mediterranean tree frogs, Hyla gr. meridionalis Boettger, 1874 (Anura: Hylidae) are widespread around the Western Mediterranean Basin, where they naturally occur across the Maghreb (Morocco, Algeria, Tunisia). Individuals of diverse Moroccan origins have been introduced and have expanded throughout the Iberian Peninsula, southern France and northern Italy (Liguria), but also on the Canary and Balearic archipelagos (Recuero et al. 2007; Dufresnes et al. 2019). Early molecular studies uncovered several mitochondrial lineages and suggested a major cryptic diversification within this taxon, with Tunisian and eastern Algerian (Numidia) populations carrying deeply divergent haplotypes compared with the rest of the range (Recuero et al. 2007; Stöck et al. 2008; Stöck et al. 2012). While intron markers showed little differentiation (Stöck et al. 2008; Stöck et al. 2012), genome-wide data obtained from RAD-sequencing have supported the deep split suspected from mtDNA (Dufresnes et al. 2018).